PERANAN PERILAKU PIMPINAN PARTAI POLITIK TERHADAP KEMAJUAN PARTAINYA - Salasiah Salasiah (Prodi Ilmu Administrasi Negara, 2017)
A party system is called solid and adaptable, if it is able to absorb and unite all the new social forces that arise as a result of modernization. From this point of view, the number of parties will only be important if it affects the capacity of the system to establish the institutional channels necessary to accommodate political participation.The purpose of this study is to find out how the Golkar Party holds consistency to reject the Perppu Pilkada according to the National Conference of Jakarta which is contrary to the attitude of the Chairman of the Golkar Party DPP. Inconsistent attitude Ical responded to the DPP Golkar Party's results Munas in Jakarta, Ace Hasan Syadzily, who then asked all cadres for level I and II to no longer believe in Ical and assume Ical has denied the confidence of participants in the event that Bali asked Ical refuse Perppu Pilkada.In this case we can imagine how Golkar will be managed over the next five years if party policy easily changes without the correct organizational mechanism. Ical underestimated the aspirations of Golkar officials who have supported him in Bali.The researcher suggests that the party must be consistent and what is decided in the National Congress must be obeyed and executed. With strong character, the Golkar Party will be solid. On the contrary if it is not consistent or mencla-mencle then the party becomes fragile and dissolved. Holding the principle for the party Is a law of nature means that if strong holds commitment he will be glorious and respected.